(untitled) (PerCursos, 2021)
The study discusses the use of the territory by the Fuduwaadunha communitie, in the region of Auarís in the Yanomami Indigenous Land, in Roraima. The Ye’kuana people live in this region. After the 1960s, the Auaris region underwent changes in landscape and territorial occupation with the arrival of non-indigenous agents, initially the Evangelical Mission of the Amazon (MEVA) and, later, the National Health Foundation (FUNASA), the National Indian Foundation (FUNAI) and the Brazilian Army (Special Border Platoon-PEF). These new actors led to changes in the form of use and occupation of the territory for the people who live there and, in this context, the article seeks to understand the uses of the territory in the regions, and the challenges they have faced in a new context. Among the challenges are the management of the territory in the face of population growth and an increase in communities in the region, with the opening of new areas for agricultural production and conflicts over the use of natural resources (hunting, fishing, extractivism), as well as weaknesses in the limits between social groups.